2016
DOI: 10.1016/j.ijlp.2015.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Examining professionals' perspectives on sexuality for service users of a forensic psychiatry unit

Abstract: Very little is known about the sexual activities of psychiatric patients during their stay in hospital and beyond. In this article, we have explored how mental health professionals working within a forensic psychiatric unit construct the issue of patient sexuality in order to ascertain the range of sexual possibilities open to patients. Drawing on interviews with twenty four participants--psychiatrists and clinical psychologists (clinical staff), we examined how participants made sense of patient sexuality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(44 citation statements)
references
References 32 publications
0
42
0
2
Order By: Relevance
“…It has been suggested that secure mental healthcare services in the UK are particularly prohibitive when it comes to inpatient sexual expression, compared to services in some other European countries (Tiwana, McDonald and Völlm 2016). In the UK, policies to determine how staff should respond to inpatient sexual expression are influenced largely by the attitudes and beliefs held by locally-employed clinicians and other staff members (Dein et al 2016;Mossman, Perlin and Dorfman 1997). Beliefs that people in secure forensic mental healthcare should have sexual agency may conflict with beliefs held by some staff that inpatients are undeserving of such freedom, given their offending history (Dein et al 2016;Ruane and Hayter 2008).…”
Section: Staff Attitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that secure mental healthcare services in the UK are particularly prohibitive when it comes to inpatient sexual expression, compared to services in some other European countries (Tiwana, McDonald and Völlm 2016). In the UK, policies to determine how staff should respond to inpatient sexual expression are influenced largely by the attitudes and beliefs held by locally-employed clinicians and other staff members (Dein et al 2016;Mossman, Perlin and Dorfman 1997). Beliefs that people in secure forensic mental healthcare should have sexual agency may conflict with beliefs held by some staff that inpatients are undeserving of such freedom, given their offending history (Dein et al 2016;Ruane and Hayter 2008).…”
Section: Staff Attitudesmentioning
confidence: 99%
“…In the UK, policies to determine how staff should respond to inpatient sexual expression are influenced largely by the attitudes and beliefs held by locally-employed clinicians and other staff members (Dein et al 2016;Mossman, Perlin and Dorfman 1997). Beliefs that people in secure forensic mental healthcare should have sexual agency may conflict with beliefs held by some staff that inpatients are undeserving of such freedom, given their offending history (Dein et al 2016;Ruane and Hayter 2008). Regardless of professional background, staff tend to be unaware of policies concerning the management of inpatient sexuality, and generally assume that they do not exist (Dein et al 2016).…”
Section: Staff Attitudesmentioning
confidence: 99%
“…But it just causes a lot of arguments when things get exchanged". Most forensic settings prohibit sexual contact between residents predicated on the perceived risks of harm, pregnancy, exploitation and detrimental therapeutic impacts despite there being "no evidence that the prohibition of sexual contact on psychiatric wards will improve the safety of inpatients" (Dein et al, 2016).…”
Section: Superordinate and Subordinate Themesmentioning
confidence: 99%
“…Staff attitudes were identified as restrictive for residents. These were described as authoritarian, conservative and enforcing conformity (Dein et al, 2016;Holmes, 2005). It was largely the attitudes of staff that prevented sexual expression between residents (Ruane & Hayter, 2008).…”
Section: Superordinate and Subordinate Themesmentioning
confidence: 99%
See 1 more Smart Citation